Curriculum Development Mechanism: An Analysis Adaptation of the Merdeka Curriculum in Elementary Schools - Rini Zakiah Baso; Rahma Ashari Hamzah; Komen Tatroman (Madako Elementary School, 2024)
The curriculum as a fundamental component of the education system, plays a central role in influencing both the learning process and student outcomes. This study aims to examine the mechanisms involved in curriculum preparation using the library research method, which involves the systematic collection and analysis of relevant information from various sources of literature to provide a comprehensive overview of the process. The study begins with an analysis of the needs for curriculum preparation, the absorption of aspirations, curriculum design, prototype trials, revisions and improvements, and the evaluation of curriculum implementation in elementary schools. The data sources used in this study include books, journals, and scientific articles. The findings of this study reveal that curriculum preparation involves several complex stages and requires collaboration among various stakeholders. The results of the analysis indicate that the adaptation of the Merdeka Curriculum requires a more flexible, responsive, and holistic approach to curriculum design. Therefore, this research makes a significant contribution by providing valuable insights into the development of a more effective curriculum preparation mechanism, one that can optimally and diversely meet the learning needs of students.